Screening rice blast-resistant cultivars via synchrotron fourier transform infrared (SR-FTIR) microspectroscopy - Phansak, Piyaporn; Siriwong, Supatcharee; Sangpueak, Rungthip; Kanawapee, Nantawan; Thumanu, Kanjana; Buensanteai, Natthiya (Emirates Journal of Food and Agriculture, 2021)
In Asia, one of the most important cereal crops is rice. Presently, a fungal pathogen called rice blast (Magnaporthe grisea) is the most devastating diseases affecting this valuable human staple. One of the ways growers can control rice blast is by chemical fungicides; however, the down side to using chemicals is the increase of production cost, environmental contamination, and loss of chemical efficacy over time. The use of resistant rice cultivars provide fungal suppression and have a positive impact on the environment. The objective of this study was to screened rice blast-resistant cultivars via SR-FTIR microspectroscopy and compare it to the traditional method. At 14 days after pathogens inoculation (DAPI) of 80 cultivars and two reference cultivars, the leaves of inoculated plants showed elliptical or spindle-shaped lesions with pointed ends, gray or white centers, and dark-green to reddish-brown margins, with an occasional yellow halo. The results of disease severity were classified as susceptible (17 cultivars), moderately susceptible (28 cultivars), and resistant group (35 cultivars) of all 80 varieties of rice. Rice cultivar no. 34 had the lowest level of disease severity, which was 6.66 ± 11.54%. Furthermore, we evaluated the accumulation of salicylic acid (SA) in rice at 24 DAPI compared with uninoculated plants. The results of the resistant group showed an increase of SA level at 24 DAPI as well as reference resistant cultivars. Rice cultivar no. 34 had SA level of 15.19 68 μg g-1 fresh weight and all other reference-resistant cultivars had a SA level at 14.70 μg g-1 fresh weight, respectively. Additionally, screening rice blast-resistant cultivars via SR-FTIR microspectroscopy revealed altered variation in biochemical components of the plants after infection. A comparison of the susceptible, moderately susceptible, and resistant cultivars revealed differences in the biochemical components of rice tissues, which may be correlated with plant defense responses to disease. These outcomes could help breeding programs in terms of the selection of resistant-rice cultivars. Keywords: biochemical change; rice; rice blast disease; salicylic acid; SR-FTIR